Short prereduced anaerobically sterilized (PRAS) biochemical scheme for identification of clinical isolates of bile-resistant Bacteroides species. - Citron, D M (1990)
The rapid identification of isolates of bile-resistant Bacteroides species has clinical and therapeutic relevance because of differences in their patterns of susceptibility and virulence. Five hundred twenty-one strains of bile-resistant Bacteroides species that were previously identified by conventional biochemical methods were reexamined to determine the minimum essential parameters necessary for correct identification. Rapid tests for bile resistance, indole production, and catalase were combined with a novel scheme for biochemical determination of saccharolytic activity on arabinose, trehalose, rhamnose, and/or xylan that included the postincubation addition of bromthymol blue for visual pH determination. Organisms were inoculated into prereduced anaerobically sterilized (PRAS) carbohydrates directly from plates, and identification was complete within 24 h of obtaining a pure culture. Ninety-three percent of bile-resistant Bacteroides species from routine clinical specimens were identified correctly by this scheme; a small number of other indole-positive strains, B. splanchnicus, B. eggerthii, and B. stercoris, were misidentified as B. uniformis.